The truth advantage : the 7 keys to a happy and fulfilling life - Wiehl, Lis W.; Littlefield, Bruce (Bruce Duanne). (Hoboken, N. J. : John Wiley & Sons, 2012)
'A New York Times bestselling author and television personality shows you how to use the truth to your advantage in every aspect of your life. From'I have a headache' to'I don't remember that,' studies show that most of us lie once or twice a day. While some lies are considered'white lies,' other lies can destroy relationships, careers, and lives. In this helpful and fascinating book, Lis Wiehl shows just how and why the truth is a powerful tool. Using news stories, court cases, and personal anecdotes, she teaches you the seven ways to unlock the Truth Advantage and gives you practical techniques to improve all aspects of your life, from your job to your relationships. This book will also equip you with your own personal lie detector, the secret to finding out when people are not telling you the truth, and then gives you advice on precisely what to do when that happens. Master the truth to your advantage. Discover how to win by telling the truth. Become your own personal lie detector and spot the clues of dishonesty. Lis Wiehl shares her knowledge as a lawyer and news commentator (and the daughter of an FBI agent) to help you sort through the lies and get to the truth. When you tell the truth and can get the truth from others, you are well liked and respected, and your life is happier. This book will help you become the best, most powerful person you can be by using one uncomplicated tool--the Truth Advantage'--
Includes bibliographical references and index.
Keywords: Truthfulness and falsehood; Deception